Pengaruh Penggunaan Lahan dan Penterasan pada Berbagai Kemiringan Lereng Terhadap Ketebalan Lapisan A, Porositas dan Permeabilitas di DTA Cikumutuk SubDAS Cimanuk Hulu Kabupaten Garut - Rizky Febria; Rija Sudirja; Maya Damayani (Fakultas Pertanian Universitas Padjadjaran, 2014)
The aimed of this research was to find out the influence of land use and terrace of slope steepness on thickness of A layer, porosity and soil permeability in Cikumutuk Catchment area of Sub-Watershed Upper Cimanuk, District of Garut. Research carried out in March 2012 until July 2012. Soil samples were taken at three different types of land uses, such as shrubs, mix plantation and dry cultivated area. Each land use consists of terrace with three slope classes, such as 8-15 %, 15-25 % and 25-40 % with reflication as much as 3 times, so the generated 27 soil samples. The method used in this research was survey method with physiographic approach, sampling technique used stratified purposive sampling, and comparative descriptive method to analyze the result. Analysis of varians test showed that dry cultivated area with terrace on all slopes give on average the lowest influence on the thickness of A layer. Dry cultivation area with terrace on slope 25-40 % had the lowest porosity and soil permeability. The value of porosity was 53.50 % and soil permeability was 8,20 cmh-1. Correlation between the parameter showed that there was no correlation between thickness of A layer and porosity (0.30ns), the thickness of a layer of A with the permeability (r = 0.13ns), while the relationship porosity with permeability (r = 0.31ns).